Bilateral obturator herniae and associated femoral hernia. Issue 669 (July 1981) - Watkins, R. M.; Leach, R. D.; Ellis, H.
Abstract : A case of a strangulated obturator hernia associated with a strangulated femoral hernia is reported. The development of obturator herniae and their association with other herniae are discussed.